Leading in the Digital Era: How Competencies, Knowledge Sharing, and Happiness Drive Virtual Team Effectiveness - Mahin, Maram; Abourokbah, Safinaz; Bajaba, Saleh (Journal of Knowledge Management Practice, 2025)
This study explores how digital leadership competencies (DLCs) affect virtual team effectiveness (VTE), highlighting the mediating roles of knowledge sharing and workplace happiness. Using data from 191 employees in Saudi Arabia and PLS-SEM, IPMA, and NCA analyses, the findings show that DLCs—like digital communication, trust, and engagement—boost VTE directly and indirectly. Results reveal that cognitive (knowledge sharing) and emotional (happiness) mechanisms both play key roles. The study offers an integrated model grounded in Social Exchange Theory and provides practical insights for developing leadership skills to enhance collaboration and well-being in digital work environments.
Keywords: knowledge management; digital leader; competencies; virtual team; knowledge sharing; happiness at work; social exchange theory